Factors influencing the sustainability of university-incubated agribusinesses: the role of stigma failure, personality and motivation in Kenya - Racheal Gladys Nakiganda; Dickson Otieno Okello; Hillary Kiplangat Bett (Cogent Business & Management)
This study explored the motivations behind university students’ participation in university incubation programs (UIPs), and examines how in addition, personality and stigma failure impact the sustainability of their agribusiness. Using a multistage sampling technique, 272 student respondents from seven universities were selected. The data were analysed through Principal Component Analysis (PCA) to identify key motivational dimensions. Results revealed two principal components: students are motivated by neccessity than opportunity factors when joining UIPs. These factors, along with personality traits and fear of failure, were further analysed using the Structural Equation Model under the Partial Least Square method. A p-value of 0.000 revealed positive and significant relationship between necessity-driven motivations and agribusiness sustainability. Additionally, a p-value of 0.000, showed a significant relationship between personality traits and sustainability. Conversely, opportunity motivation factors had no significant relationship to the sustainability of agribusinesses (p-value = 0.831). To enhance the success of incubated agribusinesses, training programs should focus on necessity-driven motivations, while policymakers should consider interventions that reduce unemployment by institutionalizing UIPs. These could lower entrepreneurial opportunity cost and encourage more students to engage in sustainable agribusiness ventures.